The Effect of Conflict-Cognitive Strategy in Inquiry Learning towards Pre-Service Teachersâ€™ Critical Thinking Ability (Jurnal Pendidikan IPA Indonesia, 2019)
The trend of todayâ€™s learning goals for educational institutions is to produce pre-service teachers who think critically. Critical thinking is a higher-order thinking domain that can be taught through appropriate learning strategies. This study intended to describe the influences of the conflict-cognitive strategy in the inquiry-based learning model towards pre-service teachersâ€™ critical thinking ability. This is pre-experimental research with one group pretest-posttest design. The sample included 18 pre-service physics teachers at Mataram State Islamic University (UIN Mataram). The pre-service-teachersâ€™ critical thinking ability was assessed using a critical thinking skill test instrument adapted from the Ennis-Weir Critical Thinking Essay Test. Indicators of critical thinking ability consisted of the ability to analyze, inference, evaluate, and make a decision. The data on critical thinking ability were analyzed descriptively and statistically, where homogeneity, normality, and t-test were performed. Descriptive analysis results indicated that the average score of critical thinking ability in the pretest was -1 in the â€œless criticalâ€ criteria and increased at posttest to 9,89 in the â€œquite criticalâ€ criteria after learning using the conflict-cognitive strategy in the inquiry-based learning model. Statistically, the analysis results revealed that the implementation of the conflict-cognitive strategy in the inquiry-based learning model had a significant effect on pre-service teachersâ€™ critical thinking ability. Therefore, the conflict-cognitive strategy in the inquiry-based learning model can be a reference and alternative learning strategy that can be implemented for specific purposes to improve pre-service teachersâ€™ critical thinking ability.